Efficacy and safety of Chinese patent medicine for urinary tract infections: a systematic review and network meta-analysis - Zhao, Jialei; Tang, Haibin; Xu, Rutong; Chen, Gang (Frontiers in Medicine, 2025)
IntroductionChinese patent medicines (CPMs) have garnered increasing attention as therapeutic options for urinary tract infections (UTIs); however, robust evidence supporting their efficacy remains limited. To address this gap, we performed a network meta-analysis (NMA) incorporating both direct and indirect comparisons to systematically evaluate and rank the efficacy and safety profiles of CPMs for UTIs.MethodsWe systematically searched five electronic databases from their inception through April 2025. Data were analyzed using a frequentist approach with random-effects models.ResultsTwenty-three studies with nine types of medicines and 3,250 patients were included in this study. While network meta-analysis suggested that Xueniaoan capsule with antibiotics (XNA_Ab) had the highest probability of being optimal, this conclusion requires cautious interpretation because of the low certainty of evidence from the included studies.ConclusionSeveral CPMs demonstrate potential therapeutic benefits for UTIs; however, these preliminary findings require validation through rigorously designed large-scale randomized controlled trials.